Flexible Loyalties: How Malleable Are Bicultural Loyalties? - Chiou, Andy Y.; Mercado, Brittany K. (Frontiers in Psychology, 2016)
Biculturals are individuals who are acculturated in two cultures and have dual identities. Due to this, many early discussions on biculturalism argued that biculturals may have divided loyalties between their two cultural backgrounds and the identities derived from these backgrounds. This view is further highlighted given historical and contemporary debate regarding immigrants in the European and American political arenas. These concerns illustrate two possibilities. First, that biculturals have a preference for their home or host culture, identifying one as the in-group to express loyalty toward and the other as the out-group. Second, biculturals may alternate between who they identify as their in-group depending upon the circumstances. In a particular cultural environment, a given bicultural may feel greater degrees of loyalty toward that culture, while feeling different loyalties when immersed in a different cultural environment. To-date, few empirical studies have examined these two questions in detail. We proposed two hypotheses: First, biculturals will express higher levels of loyalty for a specific culture if they have been exposed to a prime congruent with that culture than if they have been exposed to a prime associated with a different culture. Second, the magnitude of preferences expressed for the two cultures will differ depending on the cultural prime. We experimentally investigated this phenomenon in a sample of Chinese-Americans (N = 136) using a computer simulated soccer game between the United States and China. This simulation was selected in order to avoid the controversial nature of an immigration or cultural conflict scenario. Past research has shown that support for the sports team of a given country is a form of expressing loyalty. Participants were randomly exposed to one cultural priming condition (American, Neutral, Chinese) using commentaries recorded in different languages: English, no commentary, and Chinese. Participants were then asked to what degree they would cheer for each team. Participants expressed more likelihood to cheer for the Chinese team than for the American team. However, our results indicate that cultural priming does influence the degree to which the participants express loyalty for the Chinese team over the American team in the form of rooting behaviors.